Outcome Assessment of Open Foot Injuries in A Teaching Hospital in Ghana - Dominic, Konadu-Yeboah; Peter, Konadu; Ampem, Darkwa; Virtue, Fiawokome De-gaulle; Holdbrook, Smith; Robert, Ekow Quansah (Journal of Preventive Medicine And Care, 2019)
Purpose Foot injuries are common in low- and middle-income countries and continue to increase in incidence due to the surge in the use of motorcycles as means of transport.Yet, there is scanty data on the incidence and outcomes of treatment of open injuries to the foot in the developing world.We aimed to determine the incidence and functional outcomes of open foot injuries that are treated in a teaching hospital in Ghana. Methods We used a structured questionnaire to record the type of open foot injury, the mechanism of injury, any concomitant injuries, the time interval between injury and arrival at the hospital for treatment as well as the type of treatment instituted. Recruited patients were followed up for six months, complications resulting from the injury or its treatment were recorded for each patient. The function of the foot after healing of the injury was measured using a questionnaire-based visual analogue outcome scale of the American Foot and Ankle Society. Regression and chi-square analysis were used to evaluate potential associations. Results Over a four-month period, a total of 81 cases of open injuries to the foot were recorded. Out of this figure, 55 patients (67.9%) were males and 26 (32.1%) were females. It was found, that 66.7% aged between 19 and 49 years, 76.5% of the injuries occurred on the road and 29.7% was motor cycle related. Pedestrians are the most afflicted (61.7%). The treatment outcomes of traumatic amputations, open phalangeal fractures, dorsal skin degloving and lacerations were good. Gustillo-Anderson grade IIIB open fractures with associated plantar skin degloving had the worst outcomes with residual pain on weight bearing, bigger foot, inability to wear previous shoes and inability to tiptoe on the affected foot. Conclusions Open injuries to the foot are common in Ghana and exert a significant health burden, particularly on active young males. Long term disability may occur, even after adequate treatment of open fractures involving the foot.
Keywords: Open fracture; Gustillo-Anderson classification system; degloving injury